The relationship between biomechanical indicators of strokes and individual styles of play in tennis on the example of the best Ukrainian tennis players - Yevtyfieva, Iryna Igorivna; Borysova, Olha; Boreiko, Natalia; Yevtyfiiev, Andrii Sergiyovych; Donets, Yurii; Zinchenko, Lina (Kharkiv State Academy of Physical Culture, 2024)
Purpose. Study of the relationship between biomechanical indicators of striking technique and individual styles of play in tennis on the example of the best Ukrainian tennis players. Material and methods. For this study, 10 leading Ukrainian tennis players aged 18-30, who occupy high positions in national and international rankings, were selected. All participants of the study are professional athletes who regularly participate in international tournaments WTA and ITF. Offial match statistics were obtained from tournament organizers, which used high-resolution video cameras positioned around the courts to capture movement from diffrent angles and included pitch speed, unforced errors, fist serve hit percentage, number of points won from fist serve, and other technical metrics. The results of the study were processed using the IBM SPSS Statistics 23 statistical program. To check normality The chi-square criterion was used to assess the correspondence of the empirical distribution of the data to the theoretical normal distribution. Descriptive statistics were performed for each biomechanical parameter measured, including the arithmetic mean (x̄), standard deviation (S) and standard error of the mean (m). To visualize and analyze the biomechanical parameters of tennis players, the Python programming language with the Seaborn and Matplotlib libraries was used. Further, univariate analysis of variance (ANOVA) was used to compare the mean values of biomechanical parameters between groups of tennis players with diffrent styles of play. For an in-depth analysis of the data, a factor analysis was carried out using the principal component method and Varimax rotation with Kaiser normalization. This made it possible to identify the main factors that have the greatest impact on the technique and tactics of tennis players, as well as to determine the individual factor structure of results for each athlete. Results. In the work, an initial assessment of the technical training of athletes was made and diffrences between aggressive, defensive and universal styles of play of leading domestic tennis players were identifid. Based on the data obtained, a heat map was created that visualizes the relationships between biomechanical indicators and playing styles of tennis players. The Single-Factor Analysis of Variance (ANOVA) revealed statistically signifiant diffrences between groups of female tennis players with diffrent playing styles, highlighting the importance of individual indicators for of every style. Factor analysis using the principal component method and Varimax rotation with Kaiser normalization helped to isolate fie key factors: the force and speed of the strokes, the technical precision and control, the flxibility and adaptability of the shots, the timing and preparation, and the accuracy and stability of the rotation. Each of these factors reflcts important aspects of finess that are crucial for the successful performance of female athletes. Conclusions. The study made it possible to identify key biomechanical indicators that affct the individual styles of play of tennis players, to determine the main components of finess using factor analysis. Taking into account the unique biomechanical characteristics of tennis players will help improve technical training, increase the overall performance and competitiveness of athletes in competitions. An individual approach based on objective data will optimize the time and resources aimed at development of the most important aspects of the game, which will certainly have a positive impact on the success of tennis players' performances at a high level.
Keywords: biomechanical indicators; style of play; analysis of variance; tennis players; factor analysis